Pengelompokan Film Berdasarkan Alur Cerita menggunakan Metode Self Organizing Maps dan Silhouette Coefficient - Wilis Biro Syamhuri; Muhammad Tanzil Furqon; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Movie is one of the most popular entertainment media around the world by presenting interesting audio and visuals. Now movies can be easily accessed via streaming service provider sites or applications, even with mobile devices. The site or application that provides movie streaming service has one simple but very useful feature namely movie grouping, which are generally based on genre, year, rating, country of origin, and others. Each movie has its own unique plot or storyline, but there are several movies that have similar plots in some parts. Regardless of the same genre, sometimes there are movies that have different plots. Vice versa, there are movies with different genres but have similarities in plots. On the basis of these problems, this research grouped movies based on similarities in plots. Grouping is done using the Self Organizing Maps clustering method. After that, the results of the clustered movies were evaluated using the Silhouette Coefficient method. A total of 800 movies were successfully grouped into 25 clusters with the highest evaluation result of 0.175. One out of twenty-five clusters has the highest local evaluation score of 0.714. The results of this evaluation indicate that grouping movies based on plots is still not fully effective because only one out of twenty-five clusters produces an evaluation value in the "strong structure" category.